Study of lactose–fermenting yeasts kluyveromyces lactis for whey and apple pectin mixture fermentation - Grek, Olena; Chepel, Natalia; Krasulya, Olena (My University, 2016)
This study was carried out by using whey and apple pectin in the fiber mixture as fermentative medium in order to evaluate the biochemical activity of lactose–fermenting of some Kluyveromyces lactis strains during fermentation. The fermentation medium contained whey and apple pectin in the fiber in the ratio 9:1. It was investigated ten lactose–fermenting Kluyveromyces lactis strains coded 42 K, 95, 300, 304,317, 318, 325, 469, 868–K and 2452. During cultivation in aerobe conditions the biomass yield was the highest by yeasts cultivation in whey and apple pectin in the fiber mixture with Kluyveromyces lactis 868–K strain (71.3˟106 CFU/ml). Maximal biomass accumulation of Kluyveromyces lactis 868–K strain was achieved on the 30 h of cultivation at a temperature of 30±2 С. But addition of apple pectin in the fiber into whey caused lactose–fermenting yeasts growth inhibition (in exponential multiplication phase 1.59 % less biomass accumulation comparing with sample without apple pectin in the fiber).During the alcoholic fermentation the dynamic of CO2 accumulation positively is correlated with dynamic of biomass accumulation. Maximal CO2 content and ethanol content were observed after 30 h of fermentation at optimal temperature of 32 С. The best contents of higher alcohols, aldehydes and esters were obtained in whey and APF fermented beverage by using Kluyveromyces lactis 868–K strain which consist of low contents of n–propane (1.84 mg/l), isobutane (29.30 mg/l), acetaldehyde (27 mg/l), and high contents of 2–methyl–1–butanol (73.52 mg/l), 3–methyl–1–butanol (211.11 mg/l), methylacetate (10.61 mg/l) and ethylacetate (85.11 mg/l).
Keywords: apple pectin; яблучний пектин; яблочный пектин; whey; сироватка; сыворотка; fermented beverages; ферментовані напої; ферментированные напитки; кафедра технології молока і молочних продуктів